Conhecimento(s) dos alunos sobre ligação Química: Uma sequência didática em foco - Reis, Diones Bento dos (2017)
Chemistry is a very beautiful and fascinating science, but unfortunately little understood by the students. Still has great resistance, especially in high school students, even in elementary school when there are the first contacts with Chemistry. In this way, the present research has a qualitative character, aiming the analysis of the performance of the students of the 1st year of high school, after the application of a Didactic Sequence developed in 6 (six) classes (stages), in the teaching of Chemical Links. We used a pre - questionnaire composed of closed questions, it contained information about the research object in order to have a previous check of the students' knowledge. We used a field diary, where the speeches of some students and teachers were recorded. We request a textual production on the subject addressed. And finally, we apply a final written activity from the molecular models elaborated by the students representing the types of Chemical Bonds. In the subjective questions (textual production and final activity) the discourse analysis was used and the objective questions (questionnaire) were put through graphs and table, and later discussed. We also used discourse analysis for the speeches of students and teachers registered during the application of the Didactic Sequence. Likewise, in the final activity we construct a framework where we perform the synthesis of the students' responses. Also, the recorded images of the students during the accomplishment of the activities of the Didactic Sequence were discussed. The results indicate that the students liked the didactic proposal, favoring the teaching- learning process. We can conclude that the objectives were reached, since the students were able to critically position themselves and conceptualize some processes of the content of Chemical Bonding. We can also see that the Didactic Sequence is an important resource in the teaching-learning process, and can be applied in the classroom as a "motivational and aids tool" for the students, once it is worked on in an active perspective, promoting dialogue of the subject) of the students among themselves, leading them initially about the content addressed, intending to awaken their autonomous ability to question the world around them.